Difficult atheism post-theological thinking in Alain Badiou, Jean-Luc Nancy and Quentin Meillassoux - Watkin, David 1941-2018 (Edinburgh University Press, 2011)
Difficult Atheism shows how contemporary French philosophy is rethinking the legacy of the death of God in ways that take the debate beyond the narrow confines of atheism into the much broader domain of post-theological thinking. Christopher Watkin argues that Alain Badiou Jean-Luc Nancy and Quentin Meillassoux each elaborate a distinctive approach to the post-theological but that each approach still struggles to do justice to the death of God